Electroluminescent material and preparation method and application thereof

By connecting triarylamine and aromatic ring at 2 and 4 positions on the 9-methyl-9-phenylfluorenyl group to form a low-energy electroluminescent material, the problem of insufficient luminescence efficiency and lifetime of OLED devices is solved, and higher luminescence efficiency and longer lifetime are achieved.

CN119241373BActive Publication Date: 2025-03-25JILIN OPTICAL & ELECTRONICS MATERIALS CO LTD +1

Patent Information

Application Number
CN202411760426.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-03
Publication Date
2025-03-25
Estimated Expiration
2044-12-03

AI Technical Summary

Technical Problem

Existing OLED devices have shortcomings in terms of luminescence efficiency and working life, especially the high hole transmission energy barrier and low migration rate, resulting in low luminescence efficiency and short service life.

Method used

By connecting the triarylamine to the aromatic ring at 2,4 positions on the basis of the 9-methyl-9-phenylfluorenyl group, an electroluminescent material with a low energy level is formed. This material can reduce hole transport barriers, improve migration rates, and improve device life by introducing groups with high-triple-twisted energy levels.

Benefits of technology

It achieves the reduction of hole transmission barriers, improves luminous efficiency and migration rate, and significantly improves the life of OLED devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119241373B_ABST
    Figure CN119241373B_ABST
Patent Text Reader

Abstract

The present invention belongs to the field of organic photoelectric materials, and discloses an electroluminescent material and its preparation method and application. The structure of the electroluminescent material is shown in Formula I:. The electroluminescent material compound provided by the present invention is based on the 9-methyl-9-phenylfluorene group, and the triarylamine is connected to the aromatic ring through the 2,4 positions. When the triarylamine group is substituted with aromatic groups, the energy level is low, which avoids the localization of carrier migration, can reduce the hole transmission energy barrier, thereby improving the migration rate and the luminous efficiency; the triarylamine has excellent hole transmission performance, and the triarylamine material is used as a luminescent auxiliary layer, and a group with a high triplet energy level is introduced, which can reduce the energy difference between energy levels and greatly improve the life of the device.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of organic photoelectric materials, and specifically relates to an electroluminescent material and a preparation method and application thereof. Background Art

[0002] In the prior art, organic light emitting diode (OLED) as a new generation of display technology has been widely used in the display industry due to its advantages such as low cost, fast response, light weight, adjustable color and application on flexible substrates, etc. It is particularly widely used in commercial display fields such as mobile phone screens, TV screens, computer monitors, and car displays.

[0003] OLED has a multi-layer "sandwich" structure, which specifically includes electrode material film layers and organic functional materials sandwiched between different electrode film layers, including: hole injection layer (HIL), hole transport layer (HTL), light-emitting layer (EML), electron transport layer (ETL) and electron injection layer (EIL).

[0004] However, as the use scenarios of OLED devices become more and more extensive, the requirements for OLED devices are gradually increasing, especially in terms of luminous efficiency and working life. In the prior art, by localizing the carrier migration between the hole transport layer and the light-emitting layer, the hole transport energy barrier is high and the migration rate is low. Adding a light-emitting auxiliary layer between the two can improve the above problems, and at the same time, the stability and life are also effectively improved. Therefore, the development of an organic electroluminescent material and its preparation method and an organic electroluminescent device that can reduce the hole transport energy barrier, improve the migration rate, have high luminous efficiency and long life is a technical problem that technicians in this field urgently need to solve. Summary of the invention

[0005] In view of the deficiencies in the prior art, the present invention discloses an electroluminescent material and a preparation method and application thereof.

[0006] It should be noted that the electroluminescent material disclosed in the present invention is based on the 9-methyl-9-phenylfluorene group, and the triarylamine is connected to the aromatic ring through the 2,4 positions. When the triarylamine groups are all substituted with aromatic groups, the energy level is low, which avoids the localization of carrier migration and can reduce the hole transport energy barrier, thereby increasing the migration rate and improving the luminous efficiency. The triarylamine has excellent hole transport performance. The triarylamine material is used as a luminescent auxiliary layer, and a group with a high triplet energy level is introduced, which can reduce the energy difference between energy levels and greatly improve the life of the device.

[0007] In order to achieve the above object, the first object of the present invention is to provide an electroluminescent material, using the following technical solution:

[0008] An electroluminescent material having a structure of formula I: ;in,

[0009] R 3 and Substituted at the 2-position or 4-position of fluorene respectively;

[0010] R 1 Connected to the phenyl group in a ring-forming or substitution manner;

[0011] R 1 independently selected from hydrogen, deuterium, phenyl partially or fully substituted or unsubstituted by deuterium, biphenyl partially or fully substituted or unsubstituted by deuterium, naphthyl partially or fully substituted or unsubstituted by deuterium;

[0012] R 2 Independently selected from C1-C6 alkyl groups partially, fully or unsubstituted by deuterium;

[0013] R 3 Independently selected from phenyl partially, fully, or unsubstituted by deuterium, biphenyl partially, fully, or unsubstituted by deuterium, and naphthyl partially, fully, or unsubstituted by deuterium;

[0014] Ar 1 and Ar 2 They are independently selected from substituted or unsubstituted C6-C30 aryl groups and substituted or unsubstituted C6-C30 heteroaryl groups, and their heteroatoms contain at least one of O, S, N, Si and Se.

[0015] Furthermore, Formula I has the following structures of Formulas I-1 to I-10: ;

[0016] Wherein, n is an integer selected from 0, 1, 2, 3, 4, 5;

[0017] m is an integer selected from 0, 1, 2, 3, 4, 5, 6, 7, 8, 9;

[0018] p is an integer selected from 0, 1, 2, 3, 4;

[0019] q is an integer selected from 0, 1, 2, and 3;

[0020] R 2 Independently selected from methyl partially, fully or unsubstituted by deuterium, ethyl partially, fully or unsubstituted by deuterium, propyl partially, fully or unsubstituted by deuterium;

[0021] Ar 1 and Ar 2They are independently selected from substituted or unsubstituted C6-C24 aryl groups, substituted or unsubstituted C6-C15 heteroaryl groups, and their heteroatoms contain at least one of O, S, N, Si and Se.

[0022] Furthermore, R 2 independently selected from methyl which is partially or fully substituted or unsubstituted by deuterium;

[0023] Ar 1 and Ar 2 Each independently selected from the following groups that can be connected at any position; ; Moreover, the above groups may be partially or fully substituted by deuterium or unsubstituted; * indicates the position where the group is connected.

[0024] The number of carbon atoms of aryl, heteroaryl and alkyl in the terms "substituted or unsubstituted C6-C30 aryl", "substituted or unsubstituted C6-C24 aryl", "substituted or unsubstituted C6-C15 heteroaryl" and "substituted or unsubstituted C1-C6 alkyl" means the number of carbon atoms constituting the unsubstituted aryl, unsubstituted alkyl or the total number of heteroatoms and carbon atoms constituting the heteroaryl, without taking into account the number of carbon atoms in the substituent.

[0025] The term "substituted" means substituted by one, two or more substituents selected from the group consisting of hydrogen, deuterium, a halogen group, a cyano group, a trifluoromethyl group, a methyl group, an ethyl group, a n-propyl group, an isopropyl group, a butyl group, a n-butyl group, an isobutyl group, a tert-butyl group, a sec-butyl group, a 1-methylbutyl group, a 1-ethylbutyl group, a pentyl group, a n-pentyl group, an isopentyl group, a neopentyl group, a tert-pentyl group, a hexyl group, a n-hexyl group, a 1-methylpentyl group, a 2-methylpentyl group, a 4-methyl-2-pentyl group, a 3,3-dimethylbutyl group, a 2-ethylbutyl group, a 1-methylhexyl group, a phenyl group, a naphthyl group, an anthracenyl group, a phenanthrenyl group, a thienyl group, a furanyl group, a pyrrolyl group, a benzothienyl group, a benzofuranyl group, a pyridyl group, an indolyl group, a cyclopentanyl group, a cyclohexanyl group, and an adamantane group, or substituted by two or more of the substituents shown above connected to each other, or having no substituents.

[0026] Further, Formula I has any one of the structures of the following compounds 1-407, but is not limited thereto: .

[0027] The second object of the present invention is to provide a method for preparing the electroluminescent material as described above, which specifically comprises the following steps:

[0028] Under nitrogen environment, raw material A and raw material B are added to a mixed solution of toluene, ethanol and water, potassium carbonate and tetrakis(triphenylphosphine)palladium are added thereto, stirred evenly, heated to 70°C-90°C, and refluxed for reaction for 4-12h to obtain intermediate 1;

[0029] Cool down to -70℃--80℃ to dissolve raw material C in THF, slowly add n-butyl lithium to the solution of raw material C, react for 2-4h, slowly add the solution of intermediate 1 to the reaction bottle, warm to room temperature, and continue to react for 4-12h to obtain intermediate 2;

[0030] The intermediate 2 was dissolved in DCM and stirred at room temperature to dissolve, and then boron trifluoride ether was added thereto and reacted at room temperature for 0.5-2h to obtain the intermediate 3;

[0031] Dissolve intermediate 3 in THF, then slowly add t-BuOK into the reaction bottle, slowly drop raw material D into it, raise the temperature to 70°C-90°C, and react for 8-12h to obtain intermediate 4;

[0032] Under nitrogen environment, intermediate 4 is dissolved in a mixed solution of toluene, ethanol and water, raw material E is dissolved in a mixed solution of toluene, ethanol and water, the raw material E solution is slowly added to the intermediate 4 solution, potassium carbonate and tetrakis(triphenylphosphine)palladium are added thereto, stirred evenly, heated to 70°C-90°C, and refluxed for reaction for 4-12h to obtain intermediate 5;

[0033] Under nitrogen environment, intermediate 5 is dissolved in toluene, raw material F is dissolved in toluene, and then raw material F is slowly added to the intermediate 5 solution, tri(dibenzylideneacetone)dipalladium, tri-tert-butylphosphine and sodium tert-butyl alcohol are added thereto, the temperature is raised to 100°C-120°C, and the reaction is carried out for 1-4 hours to obtain intermediate 6;

[0034] Under nitrogen environment, the intermediate 6 is dissolved in toluene, the raw material G is dissolved in toluene, and then the raw material G is slowly added to the intermediate 6 solution, tri(dibenzylideneacetone)dipalladium, tri-tert-butylphosphine and sodium tert-butyl alcohol are added thereto, the temperature is raised to 100°C-120°C, and the reaction is carried out for 8-12h to obtain the chemical formula I;

[0035] The specific synthetic route is as follows: ;

[0036] Among them, R 1 , R 2 , R 3 ,Ar 1 ,Ar 2 As defined in Formula I, Hal 1 Independently selected from chlorine.

[0037] The third object of the present invention is to provide an application of an electroluminescent material, wherein the electroluminescent material as described above is applied to an organic electroluminescent device.

[0038] Compared with the prior art, the present invention provides an electroluminescent material and a preparation method and application thereof, which have the following excellent effects:

[0039] The electroluminescent material compound disclosed in the present invention is based on a 9-methyl-9-phenylfluorene group, and a triarylamine is connected to an aromatic ring at the 2 and 4 positions. When the triarylamine groups are all substituted with aromatic groups, the energy level is low, localization of carrier migration is avoided, and the hole transport energy barrier can be reduced, thereby increasing the migration rate and improving the luminous efficiency. The triarylamine has excellent hole transport performance. The triarylamine material is used as a luminescent auxiliary layer, and a group with a high triplet energy level is introduced, which can reduce the energy difference between energy levels and greatly improve the life of the device. BRIEF DESCRIPTION OF THE DRAWINGS

[0040] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the provided drawings without paying creative work.

[0041] Figure 1 is the H NMR spectrum of compound 80.

[0042] Figure 2 The H NMR spectrum of intermediate 5.

[0043] Figure 3 is the hydrogen NMR spectrum of compound 171. DETAILED DESCRIPTION

[0044] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention and the related drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0045] The invention specifically discloses an electroluminescent material and a preparation method and application thereof.

[0046] A series of palladium-catalyzed coupling reactions carried out in the present invention utilize the difference that the activity of Br is greater than that of Cl on the one hand, and on the other hand, the reaction site is controlled by controlling the reaction conditions, and the reaction is purified by column chromatography or silica gel funnel to remove by-products to obtain the target compound.

[0047] Reference to common knowledge is as follows:

[0048] "Transition Metal Organic Chemistry" (Original Sixth Edition), Robert H. Crabtree, Publisher: Shanghai East China University of Science and Technology Press, Publication Date: 2017-09-00, ISBN: 978-7-5628-5111-0, page 388.

[0049] "Organic Chemistry and Optoelectronic Materials Experimental Tutorial", Chen Runfeng, Publisher: Southeast University Press, Publication Date: 2019-11-00, ISBN: 9787564184230, Page 174.

[0050] The specific embodiments described below are only part of the embodiments of the present application, rather than all the embodiments.

[0051] The features and performance of the present invention will be further described in detail below with reference to the embodiments.

[0052] Example 1: Synthesis of Compound 80

[0053] ;

[0054] In a nitrogen environment, raw material A-80 (1.0 eq) (CAS number: 6630-33-7) and raw material B-80 (1.0 eq) (CAS number: 1046861-20-4) were added to a mixed solution of toluene, ethanol and water (V:V:V=2:1:1), potassium carbonate (2.2 eq) and tetrakis(triphenylphosphine)palladium (0.01 eq) were added thereto, stirred evenly, heated to 80°C, and refluxed for 6 hours. The reaction was detected by thin layer chromatography. After the reaction was completed, the temperature was slightly lowered, and diatomaceous earth was used for filtration to remove salt and catalyst. After the filtrate was cooled to room temperature, it was washed with water three times, the organic phase was retained, and then the aqueous phase was extracted with dichloromethane; the organic phases were combined and concentrated, and a mixed solution of dichloromethane and petroleum ether was used as an eluent, and intermediate 1 was purified by column chromatography (yield 79.4%);

[0055] Cool down to -78℃ and dissolve the raw material C-80 (1.0eq) (CAS No.: 92-66-0) in THF, ventilate 3 times, stir for 10 minutes, slowly add n-butyl lithium (1.2eq) to the solution of raw material C-80, react for 2h, slowly add the solution of intermediate 1 (1.0eq) to the reaction bottle, stir evenly, stop refrigeration, warm to room temperature, continue to react for 12h, detect the reaction by thin layer chromatography, wash three times with water after the reaction, retain the organic phase, then extract the aqueous phase with dichloromethane, combine the organic phases and concentrate, use a mixed solution of dichloromethane and petroleum as eluent, and purify by column chromatography to obtain intermediate 2 (yield 67.3%);

[0056] The intermediate 2 (1.0 eq) was dissolved in DCM, stirred and dissolved at room temperature, and then boron trifluoride etherate (5.0 eq) was added thereto, stirred evenly, and reacted at room temperature for 2 h. The reaction was detected by thin layer chromatography. After the reaction was completed, it was washed with water three times, and the organic phase was retained. The aqueous phase was then extracted with ethyl acetate. After the organic phases were combined, they were dried with anhydrous magnesium sulfate, and the solvent was removed with a rotary evaporator. A small amount of dichloromethane was used to completely dissolve the solid organic matter, and then it was slowly added dropwise to the petroleum ether solution, stirred evenly, and a precipitate was precipitated. The solid was filtered to obtain the solid, which was sequentially washed with anhydrous ethanol and petroleum ether, and dried to obtain the intermediate 3 (yield 87.0%).

[0057] The intermediate 3 (1.0 eq) was dissolved in THF, and then t-BuOK (5.0 eq) was slowly added to the reaction bottle, and the raw material D-80 (5.0 eq) (CAS No.: 74-88-4) was slowly added thereto. The temperature was raised to 90°C, and the reaction was carried out for 12 hours. The reaction was detected by thin layer chromatography. After the reaction was completed, the temperature was slightly lowered, and diatomaceous earth was used for filtration to remove salt. After the filtrate was cooled to room temperature, it was washed with water three times, and the organic phase was retained. Then, the aqueous phase was extracted with ethyl acetate; after the organic phases were combined, they were dried with anhydrous magnesium sulfate, and the solvent was removed with a rotary evaporator; a small amount of dichloromethane was used to completely dissolve the solid organic matter, and then it was slowly added dropwise to the petroleum ether solution, stirred evenly, and a precipitate was precipitated. The solid was filtered to obtain the solid, and it was rinsed with anhydrous ethanol and petroleum ether in turn, and dried, thereby obtaining the intermediate 4 (yield 83.8%);

[0058] Under nitrogen environment, intermediate 4 (1.0 eq) and raw material E-80 (1.0 eq) (CAS No.: 98-80-6) were added to a mixed solution of toluene, ethanol and water (V:V:V=2:1:1), potassium carbonate (2.2 eq) and tetrakis(triphenylphosphine)palladium (0.01 eq) were added thereto, the temperature was raised to 80°C, and the reaction was refluxed for 8 hours. The reaction was detected by thin layer chromatography. After the reaction was completed, the temperature was slightly lowered, and diatomaceous earth was used for filtration to remove salt and catalyst. After the filtrate was cooled to room temperature, it was washed with water three times, the organic phase was retained, and the aqueous phase was extracted with dichloromethane; the organic phases were combined and concentrated, and a mixed solution of dichloromethane and petroleum ether was used as an eluent, and the intermediate 5 was purified by column chromatography (yield 74.9%);

[0059] Under nitrogen environment, intermediate 5 (0.01eq) was dissolved in toluene, raw material F-80 (1.0eq) (CAS No.: 108714-73-4) was dissolved in toluene, and then raw material F was slowly added to the intermediate 5 solution, followed by venting 3 times, and tri(dibenzylideneacetone)dipalladium (0.01eq), tri-tert-butylphosphine (0.05eq) and sodium tert-butoxide (2.0eq) were added under nitrogen protection, stirred evenly, heated to 110°C, and reacted for 4h; the reaction was detected by thin layer chromatography, and after the reaction was completed, the temperature was slightly lowered, and diatomaceous earth was used for filtration to remove salt and catalyst. After the filtrate was cooled to room temperature, it was washed with water three times, the organic phase was retained, and then the aqueous phase was extracted with ethyl acetate; the organic phases were combined and concentrated, and a mixed solution of dichloromethane and petroleum ether was used as an eluent, and intermediate 6 was purified by column chromatography (yield 77.2%);

[0060] Under nitrogen environment, intermediate 6 (1.0 eq) was dissolved in toluene, raw material G-80 (1.0 eq) (CAS No.: 2051-62-9) was dissolved in toluene, and then raw material G-80 was slowly added to the intermediate 6 solution, tri(dibenzylideneacetone)dipalladium (0.01 eq), tri-tert-butylphosphine (0.05 eq) and sodium tert-butoxide (2.0 eq) were added thereto, stirred evenly, heated to 110°C, reacted for 8 h, and compound 80 (yield 80.6%) was obtained;

[0061] The obtained compound 80 was tested and analyzed, and the results were as follows:

[0062] HPLC purity: >99.5%;

[0063] Measured value ((ESI, m / Z): [M+H]+): 767.49;

[0064] Elemental Analysis:

[0065] Theoretical values ​​are: C, 92.27; H, 5.91; N, 1.82;

[0066] The test values ​​are: C, 92.08; H, 6.04; N, 1.96.

[0067] H NMR spectrum: Figure 1 shown.

[0068] Example 2: Synthesis of Compound 171

[0069] ;

[0070] In a nitrogen environment, raw material A-171 (1.0 eq) (CAS number: 6630-33-7) and raw material B-171 (1.0 eq) (CAS number: 1451393-45-5) were added to a mixed solution of toluene, ethanol and water (V:V:V=2:1:1), potassium carbonate (2.2 eq) and tetrakis(triphenylphosphine)palladium (0.01 eq) were added thereto, stirred evenly, heated to 80°C, and refluxed for 6 hours. The reaction was detected by thin layer chromatography. After the reaction was completed, the temperature was slightly lowered, and diatomaceous earth was used for filtration to remove salt and catalyst. After the filtrate was cooled to room temperature, it was washed with water three times, the organic phase was retained, and the aqueous phase was extracted with dichloromethane; the organic phases were combined and concentrated, and a mixed solution of dichloromethane and petroleum ether was used as an eluent, and intermediate 1 was purified by column chromatography (yield 79.8%);

[0071] Cool down to -78℃ and dissolve the raw material C-171 (1.0eq) (CAS No.: 108-86-1) in THF, ventilate 3 times, stir for 10 minutes, slowly add n-butyl lithium (1.2eq) to the solution of raw material C-171, react for 2h, slowly add the solution of intermediate 1 (1.0eq) to the reaction bottle, stir evenly, stop refrigeration, warm to room temperature, continue to react for 12h, detect the reaction by thin layer chromatography, wash with water three times after the reaction, retain the organic phase, then extract the aqueous phase with dichloromethane, combine the organic phases and concentrate, use a mixed solution of dichloromethane and petroleum as eluent, and purify by column chromatography to obtain intermediate 2 (yield 70.1%);

[0072] The intermediate 2 (1.0 eq) was dissolved in DCM, stirred and dissolved at room temperature, and then boron trifluoride etherate (5.0 eq) was added thereto, stirred evenly, and reacted at room temperature for 2 h. The reaction was detected by thin layer chromatography. After the reaction was completed, it was washed with water three times, and the organic phase was retained. The aqueous phase was then extracted with ethyl acetate. After the organic phases were combined, they were dried with anhydrous magnesium sulfate, and the solvent was removed with a rotary evaporator. A small amount of dichloromethane was used to completely dissolve the solid organic matter, and then it was slowly added dropwise to the petroleum ether solution, stirred evenly, and a precipitate was precipitated. The solid was filtered to obtain the solid, which was sequentially washed with anhydrous ethanol and petroleum ether, and dried to obtain the intermediate 3 (yield 85.9%).

[0073] The intermediate 3 (1.0 eq) was dissolved in THF, and then t-BuOK (5.0 eq) was slowly added to the reaction bottle, and the raw material D-171 (5.0 eq) (CAS No.: 74-88-4) was slowly added thereto. The temperature was raised to 90°C, and the reaction was carried out for 12 hours. The reaction was detected by thin layer chromatography. After the reaction was completed, the temperature was slightly lowered, and diatomaceous earth was used for filtration to remove salt. After the filtrate was cooled to room temperature, it was washed with water three times, and the organic phase was retained. Then, the aqueous phase was extracted with ethyl acetate; after the organic phases were combined, they were dried with anhydrous magnesium sulfate, and the solvent was removed with a rotary evaporator; a small amount of dichloromethane was used to completely dissolve the solid organic matter, and then it was slowly added dropwise to the petroleum ether solution, stirred evenly, and a precipitate was precipitated. The solid was filtered to obtain the solid, and it was rinsed with anhydrous ethanol and petroleum ether in turn, and dried, thereby obtaining the intermediate 4 (yield 84.2%);

[0074] Under nitrogen environment, intermediate 4 (1.0 eq) and raw material E-171 (1.0 eq) (CAS No.: 98-80-6) were added to a mixed solution of toluene, ethanol and water (V:V:V=2:1:1), potassium carbonate (2.2 eq) and tetrakis(triphenylphosphine)palladium (0.01 eq) were added thereto, the temperature was raised to 80°C, and the reaction was refluxed for 8 hours. The reaction was detected by thin layer chromatography. After the reaction was completed, the temperature was slightly lowered, and diatomaceous earth was used for filtration to remove salt and catalyst. After the filtrate was cooled to room temperature, it was washed three times with water, the organic phase was retained, and the aqueous phase was extracted with dichloromethane; the organic phases were combined and concentrated, and a mixed solution of dichloromethane and petroleum ether was used as an eluent, and the intermediate 5 (yield 76.2%) was purified by column chromatography. The hydrogen nuclear magnetic resonance spectrum was as follows: Figure 2 As shown;

[0075] Under nitrogen environment, intermediate 5 (0.01eq) was dissolved in toluene, and raw material F-171 (1.0eq) (CAS No.: 92-67-1) was dissolved in toluene, and then raw material F-171 was slowly added to the intermediate 5 solution, followed by venting 3 times, and tri(dibenzylideneacetone)dipalladium (0.01eq), tri-tert-butylphosphine (0.05eq) and sodium tert-butoxide (2.0eq) were added under nitrogen protection, stirred evenly, heated to 110°C, and reacted for 4h; the reaction was detected by thin layer chromatography, and after the reaction was completed, the temperature was slightly lowered, and diatomaceous earth was used for filtration to remove salt and catalyst. After the filtrate was cooled to room temperature, it was washed with water three times, and the organic phase was retained, and then the aqueous phase was extracted with ethyl acetate; the organic phases were combined and concentrated, and a mixed solution of dichloromethane and petroleum ether was used as an eluent, and intermediate 6 was purified by column chromatography (yield 76.7%);

[0076] Under nitrogen environment, intermediate 6 (1.0 eq) was dissolved in toluene, raw material G-171 (1.0 eq) (CAS No.: 2051-62-9) was dissolved in toluene, and then raw material G-171 was slowly added to the intermediate 6 solution, tri(dibenzylideneacetone)dipalladium (0.01 eq), tri-tert-butylphosphine (0.05 eq) and sodium tert-butoxide (2.0 eq) were added thereto, stirred evenly, heated to 110°C, reacted for 8 hours, and compound 171 (yield 82.4%) was obtained; the obtained compound 171 was detected and analyzed, and the results were as follows:

[0077] HPLC purity: >99.5%;

[0078] Measured value ((ESI, m / Z): [M+H]+): 651.41;

[0079] Elemental Analysis:

[0080] Theoretical values ​​are: C, 92.13; H, 5.72; N, 2.15;

[0081] Test values ​​are: C, 91.99; H, 5.81; N, 2.26.

[0082] H NMR spectrum: Figure 3 shown.

[0083] Example 3: Synthesis of Compound 320

[0084] ;

[0085] In a nitrogen environment, raw material A-320 (1.0 eq) (CAS No.: 6630-33-7) and raw material B-320 (1.0 eq) (CAS No.: 1046861-20-4) were added to a mixed solution of toluene, ethanol and water (V:V:V=2:1:1), potassium carbonate (2.2 eq) and tetrakis(triphenylphosphine)palladium (0.01 eq) were added thereto, stirred evenly, heated to 80°C, and refluxed for 6 hours. The reaction was detected by thin layer chromatography. After the reaction was completed, the temperature was slightly lowered, and diatomaceous earth was used for filtration to remove salt and catalyst. After the filtrate was cooled to room temperature, it was washed with water three times, the organic phase was retained, and then the aqueous phase was extracted with dichloromethane; the organic phases were combined and concentrated, and a mixed solution of dichloromethane and petroleum ether was used as an eluent, and intermediate 1 was purified by column chromatography (yield 79.5%);

[0086] Cool down to -78℃ and dissolve the raw material C-320 (1.0eq) (CAS No.: 108-86-1) in THF, ventilate 3 times, stir for 10 minutes, slowly add n-butyl lithium (1.2eq) to the solution of raw material C-320, react for 2h, slowly add the solution of intermediate 1 (1.0eq) to the reaction bottle, stir evenly, stop refrigeration, warm to room temperature, continue to react for 12h, detect the reaction by thin layer chromatography, wash with water three times after the reaction, retain the organic phase, then extract the aqueous phase with dichloromethane, combine the organic phases and concentrate, use a mixed solution of dichloromethane and petroleum as eluent, and purify by column chromatography to obtain intermediate 2 (yield 70.3%);

[0087] The intermediate 2 (1.0 eq) was dissolved in DCM, stirred and dissolved at room temperature, and then boron trifluoride etherate (5.0 eq) was added thereto, stirred evenly, and reacted at room temperature for 2 h. The reaction was detected by thin layer chromatography. After the reaction was completed, it was washed with water three times, and the organic phase was retained. The aqueous phase was then extracted with ethyl acetate. After the organic phases were combined, they were dried with anhydrous magnesium sulfate, and the solvent was removed with a rotary evaporator. A small amount of dichloromethane was used to completely dissolve the solid organic matter, and then it was slowly added dropwise to the petroleum ether solution, stirred evenly, and a precipitate was precipitated. The solid was filtered to obtain the solid, which was sequentially washed with anhydrous ethanol and petroleum ether, and dried to obtain the intermediate 3 (yield 84.7%).

[0088] The intermediate 3 (1.0 eq) was dissolved in THF, and then t-BuOK (5.0 eq) was slowly added to the reaction bottle, and the raw material D-320 (5.0 eq) (CAS No.: 865-50-9) was slowly added thereto. The temperature was raised to 90°C, and the reaction was carried out for 12 hours. The reaction was detected by thin layer chromatography. After the reaction was completed, the temperature was slightly lowered, and diatomaceous earth was used for filtration to remove salt. After the filtrate was cooled to room temperature, it was washed with water three times, and the organic phase was retained. Then, the aqueous phase was extracted with ethyl acetate; after the organic phases were combined, they were dried with anhydrous magnesium sulfate, and the solvent was removed with a rotary evaporator; a small amount of dichloromethane was used to completely dissolve the solid organic matter, and then it was slowly added dropwise to the petroleum ether solution, stirred evenly, and a precipitate was precipitated. The solid was filtered to obtain the solid, and it was rinsed with anhydrous ethanol and petroleum ether in turn, and dried, thereby obtaining the intermediate 4 (yield 84.7%);

[0089] Under nitrogen environment, intermediate 4 (1.0 eq) and raw material E-320 (1.0 eq) (CAS No.: 98-80-6) were added to a mixed solution of toluene, ethanol and water (V:V:V=2:1:1), potassium carbonate (2.2 eq) and tetrakis(triphenylphosphine)palladium (0.01 eq) were added thereto, the temperature was raised to 80°C, and the reaction was refluxed for 8 hours. The reaction was detected by thin layer chromatography. After the reaction was completed, the temperature was slightly lowered, and diatomaceous earth was used for filtration to remove salt and catalyst. After the filtrate was cooled to room temperature, it was washed with water three times, the organic phase was retained, and the aqueous phase was extracted with dichloromethane; the organic phases were combined and concentrated, and a mixed solution of dichloromethane and petroleum ether was used as an eluent, and the intermediate 5 was purified by column chromatography (yield 77.0%);

[0090] Under nitrogen environment, intermediate 5 (0.01eq) was dissolved in toluene, raw material F-320 (1.0eq) (CAS No.: 7293-45-0) was dissolved in toluene, and then raw material F-320 was slowly added to the intermediate 5 solution. Then the air was ventilated 3 times, tri(dibenzylideneacetone)dipalladium (0.01eq), tri-tert-butylphosphine (0.05eq) and sodium tert-butoxide (2.0eq) were added under nitrogen protection, stirred evenly, heated to 110°C, and reacted for 4h; the reaction was detected by thin layer chromatography. After the reaction was completed, the temperature was slightly lowered, and diatomaceous earth was used for filtration to remove salt and catalyst. After the filtrate was cooled to room temperature, it was washed with water three times, the organic phase was retained, and then the aqueous phase was extracted with ethyl acetate; the organic phases were combined and concentrated, and a mixed solution of dichloromethane and petroleum ether was used as an eluent, and intermediate 6 was purified by column chromatography (yield 77.1%);

[0091] Under nitrogen environment, intermediate 6 (1.0 eq) was dissolved in toluene, raw material G-320 (1.0 eq) (CAS No.: 90-13-1) was dissolved in toluene, and then raw material G-320 was slowly added to the solution of intermediate 6. Tris(dibenzylideneacetone)dipalladium (0.01 eq), tri-tert-butylphosphine (0.05 eq) and sodium tert-butoxide (2.0 eq) were added thereto, stirred evenly, heated to 110°C, reacted for 8 hours, and compound 320 (yield 81.9%) was obtained; the obtained compound 320 was tested and analyzed, and the results were as follows:

[0092] The obtained compound 320 was tested and analyzed, and the results were as follows:

[0093] HPLC purity: >99.5%;

[0094] Measured value ((ESI, m / Z): [M+H]+): 704.49;

[0095] Elemental Analysis:

[0096] Theoretical values ​​are: C, 92.01; H, 6.00; N, 1.99;

[0097] The test values ​​are: C, 91.86; H, 6.07; N,2.11.

[0098] Example 4-89

[0099] The following compounds were synthesized by referring to the synthesis methods of Examples 1 to 3, and tested using a Waters XEVOTQD mass spectrometer, which has low precision. The ESI source was used for testing, and the mass spectrometry test values ​​are shown in Table 1 below.

[0100] Table 1

[0101]

[0102] In addition, it should be noted that other compounds of the present application can be obtained by referring to the synthesis methods of the above-listed embodiments, so they will not be listed one by one here.

[0103] Another object of the present application is to provide an organic electroluminescent device, which may include a hole injection layer, a hole transport layer, an electron blocking layer, a light-emitting auxiliary layer, a light-emitting layer, a hole blocking layer, an electron transport layer, an electron injection layer, a capping layer, etc. as the structure of the organic layer. However, the structure of the light-emitting device is not limited thereto, and may include fewer or more organic layers.

[0104] According to one embodiment of the present specification, the compound shown in Chemical Formula I prepared in the present application is used as a light-emitting auxiliary layer material.

[0105] When manufacturing an organic light-emitting element, the compound represented by the chemical formula I may be formed into an organic layer by vacuum evaporation or solution coating, wherein the solution coating method refers to spin coating, dip coating, blade coating, inkjet printing, screen printing, spraying, roller coating, etc., but is not limited thereto.

[0106] The organic electroluminescent device of the present application may be a top emission type, a bottom emission type or a bidirectional emission type according to the materials used.

[0107] As the anode material, a material having a large work function is generally preferred so that holes can be smoothly injected into the organic material layer. Specific examples of the anode material that can be used in the present invention include: metals, such as vanadium, chromium, copper, zinc and gold, or alloys thereof; metal oxides, such as zinc oxide, indium oxide, indium tin oxide (ITO) and indium zinc oxide (IZO); combinations of metals and oxides, such as ZnO:Al or SnO 2 :Sb; conductive polymers such as poly(3-methylthiophene), poly[3,4-(ethylene-1,2-dioxy)thiophene] (PEDOT), polypyrrole and polyaniline, but not limited thereto.

[0108] The hole injection material is a material that advantageously receives holes from the anode at a low voltage, and the highest occupied molecular orbital (HOMO) of the hole injection material is preferably between the work function of the anode material and the HOMO of the surrounding organic material layer. Specific examples of hole injection materials include metal porphyrins, oligothiophenes, organic materials based on arylamines, organic materials based on hexanitrile hexaazatriphenylene, organic materials based on quinacridone, organic materials based on perylene, anthraquinone, and conductive polymers based on polyaniline and polythiophene, etc., but are not limited thereto, and may also include compounds capable of p-doping.

[0109] The hole transport material is a material that can receive holes from the anode or the hole injection layer and transport the holes to the light-emitting layer, and a material having a high hole mobility is suitable. Specific examples thereof include organic materials based on arylamine, conductive polymers, block copolymers having both a conjugated portion and a non-conjugated portion, etc., but are not limited thereto.

[0110] A luminescent auxiliary layer (multi-layer hole transport layer) is added between the hole transport layer and the light-emitting layer. The luminescent auxiliary layer mainly assists the hole transport layer, so it is sometimes also called the second hole transport layer. The luminescent auxiliary layer enables the holes transferred from the anode to move smoothly to the light-emitting layer, and can block the electrons transferred from the cathode to confine the electrons in the light-emitting layer, reduce the potential barrier between the hole transport layer and the light-emitting layer, reduce the driving voltage of the light-emitting device, and further increase the utilization rate of holes, thereby improving the luminous efficiency and life of the device.

[0111] The electron blocking layer may be disposed between the hole transport layer and the light emitting layer. As the electron blocking layer, a material known in the art, such as an arylamine-based organic material, may be used.

[0112] The light-emitting layer may emit red, green or blue light and may be formed of a phosphorescent material or a fluorescent material. The light-emitting material is a material that can emit light in the visible light region by receiving holes and electrons from the hole transport layer and the electron transport layer, respectively, and combining the holes with the electrons, and is preferably a material having a favorable quantum efficiency for fluorescence or phosphorescence. Specific examples thereof include: 8-hydroxyquinoline aluminum (Alq 3 ); carbazole-based compounds; diphenylethylene-based compounds; BAlq; 10-hydroxybenzoquinoline-metal compounds; benzocarbazole-based, benzothiazole-based and benzimidazole-based compounds; poly(p-phenylene vinylene) (PPV)-based polymers; spiro compounds; polyfluorene; rubrene, etc., but are not limited thereto.

[0113] The host material of the light-emitting layer includes fused aromatic ring derivatives, heterocyclic compounds, etc. Specifically, the fused aromatic ring derivatives include anthracene derivatives, pyrene derivatives, naphthalene derivatives, pentacene derivatives, phenanthrene compounds, fluoranthene compounds, etc., and the heterocyclic compounds include carbazole derivatives, dibenzofuran derivatives, ladder-type furan compounds, pyrimidine derivatives, etc., however, the materials are not limited thereto.

[0114] The hole blocking layer may be disposed between the electron transport layer and the light emitting layer, and a material known in the art, such as a triazine-based compound, may be used.

[0115] The electron transport layer can play a role in promoting electron transport. The electron transport material is a material that advantageously receives electrons from the cathode and transports the electrons to the light-emitting layer, and materials with high electron mobility are suitable. The electron transport layer can include an electron buffer layer, a hole blocking layer, and an electron transport layer.

[0116] The electron injection layer can play a role in promoting electron injection. The electron injection material is preferably a compound that has the ability to transport electrons, has an effect of injecting electrons from the cathode, has an excellent electron injection effect on the light-emitting layer or the light-emitting material, prevents the excitons generated in the light-emitting layer from migrating to the hole injection layer, and in addition, has excellent film forming ability. Specific examples thereof include fluorenone, anthraquinone dimethane, diphenoquinone, thiopyran dioxide, azole, diazole, triazole, imidazole, perylene tetracarboxylic acid, fluorenyl methane, anthrone, etc. and their derivatives, metal complexes, nitrogen-containing 5-membered ring derivatives, etc., but are not limited thereto.

[0117] As the cathode material, a material with a small work function is generally preferred so that electrons can be smoothly injected into the organic material layer. Specific examples of cathode materials include: metals such as magnesium, calcium, sodium, potassium, titanium, indium, yttrium, lithium, gadolinium, aluminum, silver, tin and lead, or alloys thereof; multilayer structure materials such as LiF / Al or LiO 2 / Al; and so on, but not limited to.

[0118] In addition to the light-emitting auxiliary layer disclosed herein containing chemical formula I, the other layer materials in the OLED device can use existing hole injection materials, hole transport materials, hole transport auxiliary materials, dopant materials, hole blocking layer materials, electron transport layer materials and electron injection materials.

[0119] Device Example 1: Preparation of red organic electroluminescent device

[0120] The structure of the prepared OLED device is: ITO anode / HIL / HTL / Prime / EML / HBL / ETL / EIL / cathode / CPL.

[0121] a. ITO anode: The ITO (indium tin oxide)-Ag-ITO (indium tin oxide) glass substrate with a coating thickness of 1500Å was cleaned in distilled water for 3 times, ultrasonically washed for 40 minutes, and then repeatedly cleaned with distilled water for 3 times, ultrasonically washed for 20 minutes. After washing, it was ultrasonically washed with methanol, acetone, and isopropanol in sequence (5 minutes each time), dried, and then transferred to a plasma cleaning machine for washing for 5 minutes. It was then sent to a vapor deposition machine, and the substrate was used as the anode, and other functional layers were deposited on it in sequence.

[0122] b. HIL (hole injection layer): Hole injection layer materials HT-1 and P-dopant were vacuum evaporated at a deposition rate of 1Å / s as the hole injection layer, the deposition rate ratio of HT-1 and P-dopant was 97:3, and the thickness was 10nm.

[0123] c. HTL (hole transport layer): 125 nm of HT-1 was vacuum-deposited on the hole injection layer at a deposition rate of 1.5 Å / s as the hole transport layer.

[0124] d. Prime (luminescence auxiliary layer): 100 nm of the compound 2 provided in the above embodiment was vacuum-deposited on the hole transport layer at a deposition rate of 0.5 Å / s as a luminescence auxiliary layer.

[0125] e. EML (light-emitting layer): At a deposition rate of 1Å / s, the main material (Host-1 and Host-2) and the dopant material (Dopant-1) with a total thickness of 40nm are vacuum-deposited on the light-emitting auxiliary layer as the light-emitting layer. The deposition rate ratio of the main material to the dopant material is 97:3, and the deposition rate ratio of Host-1 and Host-2 in the main material is 4:6. The chemical formulas of Host-1, Host-2 and Dopant-1 are shown below.

[0126] f. HBL (hole blocking layer): A hole blocking layer HB-1 with a thickness of 5 nm was vacuum-deposited on the light-emitting layer at a deposition rate of 0.5 Å / s.

[0127] g. ETL (electron transport layer): ET-1 and Liq with a thickness of 30 nm were vacuum evaporated on the hole blocking layer at a deposition rate of 1 Å / s as the electron transport layer, where the deposition rate ratio of ET-1 and Liq was 50:50.

[0128] h. EIL (electron injection layer): A Yb film with a thickness of 1 nm was vacuum-deposited on the electron transport layer at a deposition rate of 0.5 Å / s to form an electron injection layer.

[0129] i. Cathode: 13 nm of magnesium and silver were evaporated at an evaporation rate ratio of 1 Å / s, and the evaporation rate ratio was 1:9 to obtain a cathode.

[0130] j. CPL (light extraction layer): CPL-1 with a thickness of 60 nm was vacuum-deposited on the cathode at a deposition rate of 1Å / s as a light extraction layer.

[0131] K. Package the vapor-deposited substrate: First, use the glue coating equipment to coat the cleaned cover with UV glue, then move the coated cover to the pressing section, place the vapor-deposited substrate on the upper end of the cover, and finally bond the substrate and cover with the bonding equipment, and complete the light curing of the UV glue at the same time.

[0132] The structures of HT-1, P-dopant, Host-1, Host-2, Dopant-1, HB-1, ET-1, and CPL-1 used in the device embodiment 1 are as follows: .

[0133] Device Example 2-43

[0134] Referring to the method provided in the above device embodiment 1, compounds 11, 14, 16, 22, 34, 38, 43, 46, 48, 54, 66, 70, 75, 78, 86, 107, 144, 161, 162, 169, 171, 174, 176, 184, 193, 203, 208, 216, 226, 229, 235, 240, 252, 257, 259, 260, 267, 285, 311, 319, 321, and 399 were selected to replace compound 2, and the light-emitting auxiliary layer was evaporated to prepare the corresponding organic electroluminescent devices, which are respectively recorded as device embodiments 2-43.

[0135] Device Comparison Examples 1-8

[0136] An organic electroluminescent device is prepared according to the above-mentioned method for preparing an organic electroluminescent device, except that compound 2 in device example 1 is replaced by compounds a, b, c, d, e, f, g, h, wherein the structural formulas of compounds a, b, c, d, e, f, g, h are as follows: .

[0137] The driving voltage, luminous efficiency and lifespan of the organic electroluminescent devices obtained from the device embodiments 1-43 and the device comparative examples 1-8 were characterized at a brightness of 6000 (nits). The test results are shown in Table 2 below.

[0138] Table 2 Luminous characteristics test results (brightness value is 6000 nits)

[0139]

[0140] Device Example 44: Preparation of Green Organic Electroluminescent Device

[0141] The structure of the prepared OLED device is: ITO anode / HIL / HTL / Prime / EML / ETL / EIL / cathode / CPL.

[0142] a. ITO anode: The ITO (indium tin oxide)-Ag-ITO (indium tin oxide) glass substrate with a coating thickness of 1500Å was cleaned in distilled water for 3 times, ultrasonically washed for 40 minutes, and then repeatedly cleaned with distilled water for 3 times, ultrasonically washed for 20 minutes. After washing, it was ultrasonically washed with methanol, acetone, and isopropanol in sequence (5 minutes each time), dried, and then transferred to a plasma cleaning machine for washing for 5 minutes. It was then sent to a vapor deposition machine, and the substrate was used as the anode, and other functional layers were deposited on it in sequence.

[0143] b. HIL (hole injection layer): Hole injection layer materials HT-2 and P-dopant were vacuum evaporated at a deposition rate of 1Å / s as the hole injection layer, the deposition rate ratio of HT-2 and P-dopant was 97:3, and the thickness was 10nm.

[0144] c. HTL (hole transport layer): 130nm of HT-2 was vacuum-deposited on the hole injection layer at a deposition rate of 1.5Å / s as the hole transport layer.

[0145] d. Prime (luminescence auxiliary layer): 50 nm of the compound 1 provided in the above embodiment was vacuum-deposited on the hole transport layer at a deposition rate of 0.5 Å / s as a luminescence auxiliary layer.

[0146] e. EML (light-emitting layer): At a deposition rate of 1Å / s, dual host materials (Host-3 and Host-4) and dopant material (Dopant-2) with a thickness of 200nm were vacuum-deposited on the light-emitting auxiliary layer as the light-emitting layer. The deposition rate ratio of the host material to the dopant material was 90:10, and the deposition rate ratio of Host-3 and Host-4 in the host material was 4:6. The chemical formulas of Host-3, Host-4 and Dopant-2 are shown below.

[0147] f. HBL (hole blocking layer): A hole blocking layer HB-2 with a thickness of 5 nm was vacuum-deposited on the light-emitting layer at a deposition rate of 0.5 Å / s.

[0148] g. ETL (electron transport layer): ET-2 and Liq with a thickness of 30 nm were vacuum evaporated on the hole blocking layer at a deposition rate of 1 Å / s as the electron transport layer, where the deposition rate ratio of ET-2 and Liq was 50:50.

[0149] h. EIL (electron injection layer): A 1.0 nm Yb film layer was vacuum-deposited on the electron transport layer at a deposition rate of 0.5 Å / s to form an electron injection layer.

[0150] i. Cathode: 13 nm of magnesium and silver were evaporated at an evaporation rate ratio of 1 Å / s, and the evaporation rate ratio was 1:9 to obtain an OLED device.

[0151] j. CPL (light extraction layer): CPL-2 with a thickness of 60 nm was vacuum-deposited on the cathode at a deposition rate of 1Å / s as a light extraction layer.

[0152] K. Package the vapor-deposited substrate: First, use the glue coating equipment to coat the cleaned cover with UV glue, then move the coated cover to the pressing section, place the vapor-deposited substrate on the upper end of the cover, and finally bond the substrate and cover with the bonding equipment, and complete the light curing of the UV glue at the same time.

[0153] The structures of HT-2, P-dopant, Host-3, Host-4, Dopant-2, HB-2, ET-2, and CPL-2 used in the above device embodiment 44 are as follows: .

[0154] Device Examples 45-89

[0155] Referring to the method provided in the above device embodiment 44, compounds 3, 5, 6, 7, 13, 18, 20, 21, 24, 26, 39, 53, 58, 62, 69, 71, 80, 84, 90, 98, 114, 118, 122, 126, 135, 139, 150, 154, 273, 279, 282, 289, 290, 291, 294, 300, 301, 303, 305, 306, 309, 316, 317, 320, and 398 are respectively selected to replace compound 1, and the light-emitting auxiliary layer is evaporated to prepare the corresponding organic electroluminescent devices, which are respectively recorded as device embodiments 45-89.

[0156] Device Comparison Examples 9-16

[0157] An organic electroluminescent device is prepared according to the above-mentioned method for preparing an organic electroluminescent device, except that compound 1 in device Example 44 is replaced by compounds a, b, c, d, e, f, g, h, wherein the structures of compounds a, b, c, d, e, f, g, h are as follows: .

[0158] The driving voltage, luminous efficiency and lifespan of the organic electroluminescent devices obtained from the device embodiments 44-89 and the device comparative examples 9-16 were characterized at a brightness of 15000 (nits). The test results are shown in Table 3 below.

[0159] Table 3 Luminous characteristics test results (brightness value is 15000 nits)

[0160]

[0161] It can be seen from Table 2 and Table 3 that the performance of the device can be changed by changing the substituents and the positions of the substituents, and the luminous efficiency and life of the device can be improved to varying degrees.

[0162] It can be seen from Table 2 and Table 3 that, compared with the existing organic electroluminescent devices provided by Comparative Examples 1 to 16, the OLED device embodiments 1 to 89 prepared using the electroluminescent materials provided by the embodiments of the present invention show obvious advantages in device life, which is 10 to 15% higher than that of the comparative examples, and also have certain improvements in the driving voltage and luminous efficiency of the device.

[0163] Among them, compound 235 and compound a are compared in parallel, and compound 2 and compound b are compared in parallel. The difference between the two is that the parent nucleus is different. The 9,9-diphenylfluorene in compound b has too many phenyl groups, which will increase the packing density and steric hindrance of the compound, affect the evaporation temperature of the compound, and thus reduce the luminous efficiency and life. 9-Methyl-9-phenylfluorene has a large conjugated property. On the one hand, it can improve the stacking effect between molecules, and on the other hand, it can increase the horizontal arrangement of molecules, so that the molecules can be effectively arranged horizontally, thereby effectively increasing the luminous efficiency and greatly improving the device life.

[0164] Compound 11 and compound c were compared in parallel, and compound 171 and compound e were compared in parallel. The difference between the two groups lies in the substitution sites. The comparison compounds use 3 and 4 substitutions, and the material steric hindrance is large, which makes the comparison compounds c and e less stable, resulting in a shorter device life.

[0165] Compound 162 is compared with compound f in parallel, compound 11 is compared with compound g in parallel, and compound 16 is compared with compound h in parallel. In the present invention, compounds 11, 16, and 162 are connected with a benzene group on the phenyl group near the N atom on the triarylamine in 9-methyl-9-phenylfluorene, which prolongs the conjugated system of the compound, resulting in an increase in the mobility of the compound, thereby reducing the driving voltage and improving the luminous efficiency and life of the device.

[0166] In f, g, and h, the triarylamine and the aromatic ring are heterocyclically substituted on the parent core, resulting in an increase in the conjugated area. The increase in the conjugated area causes the interaction between molecules, resulting in an increase in the evaporation temperature and a decrease in the service life of the device.

[0167] From the above parallel comparison, it can be seen that the embodiment of the present application connects the triarylamine to the aromatic ring through the 2,4 positions on the basis of 9-methyl-9-phenylfluorene, which has a high triplet energy level, reduces the energy difference between energy levels, and increases the stability of the material. From the data in Table 2 and Table 3, it can be seen that the compounds of the present application have a longer life and better luminous efficiency in both red and green light devices.

[0168] The above description of the disclosed embodiments enables one skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to one skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.

Claims

1. An electroluminescent material, characterized in that: The structure of the electroluminescent material is as follows: ; in, R2 is independently selected from C1-C6 alkyl partially, fully or unsubstituted by deuterium; R3 is independently selected from phenyl partially substituted or fully substituted or unsubstituted by deuterium, biphenyl partially substituted or fully substituted or unsubstituted by deuterium, naphthyl partially substituted or fully substituted or unsubstituted by deuterium; Ar1 and Ar2 are independently selected from the following groups: ; n is an integer selected from 0, 1, 2, 3, 4, 5; m is an integer selected from 0, 1, 2, 3, 4, 5, 6, 7; p is an integer selected from 0, 1, 2, 3, 4; q is an integer selected from 0, 1, 2, and 3.

2. The electroluminescent material according to claim 1, characterized in that R2 is independently selected from methyl which is partially, fully or unsubstituted by deuterium, ethyl which is partially, fully or unsubstituted by deuterium, and propyl which is partially, fully or unsubstituted by deuterium.

3. The electroluminescent material according to claim 2, characterized in that R2 is independently selected from methyl which is partially or fully substituted or unsubstituted by deuterium.

4. The electroluminescent material according to claim 1, characterized in that The structure of the electroluminescent material is shown below: .

5. An application of an electroluminescent material, characterized in that: The electroluminescent material according to any one of claims 1 to 4 is applied to an organic electroluminescent device.

6. The use according to claim 5, characterized in that: The organic electroluminescent device comprises an organic layer; the organic layer contains the electroluminescent material.

Citation Information

Patent Citations

  • Compound, composition and organic light-emitting device

    CN108699025A

  • Amine compound and organic electroluminescent device thereof

    CN116891414A

Cited By

  • Light-emitting auxiliary material, preparation method thereof and laminated organic electroluminescent device

    CN121800655A

  • Light-emitting auxiliary material, preparation method thereof and laminated organic electroluminescent device

    CN121800655B